On Almost Bounded Submodules - Shihab, B. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Let R be a commutative ring with identity, and let M be a unitary R-module. We introduce a concept of almost bounded submodules as follows: A submodule N of an R-module M is called an almost bounded submodule if there exists xÃŽM, xÃN such that annR(N)=annR(x).        In this paper, some properties of almost bounded submodules are given. Also, various basic results about almost bounded submodules are considered.        Moreover, some relations between almost bounded submodules and other types of modules are considered.